Turnaround a memoir - Forman, Miloš 1932-2018; Novák, Jan 1953- (Villard Books, 1994)
"In these pages are wonderful stories of the artist as a young man: tales of finding love in a deranged Communist bureaucracy, fleeing his beloved homeland, living in the bohemian Chelsea Hotel in the late sixties, discovering free spirits in Greenwich Village, learning the peculiar ways and means of Hollywood, reaching the pinnacle of professional success, and, finally, being allowed to return home to film the life of another young genius, Wolfgang Amadeus Mozart. But above all, Forman's life story can be read as a chronicle of the bittersweet intersection of life, love, politics, and art. Frank, vibrant, passionate, Turnaround is a triumph."--BOOK JACKET
American studies series
Keywords: Forman, Miloš; Forman, Miloš -- 1932-2018; Producteurs et réalisateurs de cinéma - République tchèque - Biographies; Motion picture producers and directors -- Czech Republic -- Biography; Motion picture producers and directors -- United States -- Biography; Autobiografie; Tschechische Republik; USA; Biografie